Design development and modelling of linear permanent magnet generator topologies for wave energy conversion - Memon, A.H. (Research India Publications, 2017)
This paper presents the design development and mathematical modeling of linear permanent magnet (PM) generator topologies for wave energy conversion. Three different topologies are proposed and developed using different design configuration and are compared with conventional topology for validation purpose. Mathematical model is developed for each topology based on its geometric shape and structure, respectively. All the topologies are compared by using their corresponding mathematical models and taking into account constrained parameters of linear PM generator. Finite Element Analysis (FEA) is carried out in order to determine electromagnetic characteristics and analyze all the topologies by using their resultant data and dimensions obtained after model comparison. The main results; induced-EMF and flux-linkage for all proposed topologies are presented, which shows that Topology No.1 (Trgr-coil) has leading performance as compared to other topologies. © Research India Publications.